Penyuluhan Pentingnya Tidur Yang Cukup Bagi Anak di SD Negeri 200103 Padangsidimpuan - Nasution, Dina Rahmi Solihad; Liana; Lubis, Yuni Aflah; Nina Nazlina; Hasibuan, Rido (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Getting enough sleep is essential for a child's physical, cognitive, and emotional development. The purpose of this community service is to provide counseling on the various benefits of adequate sleep for children, which include improving academic performance, emotional balance, and physical and mental health. Lack of sleep quality can lead to a decrease in hemoglobin levels which eventually leads to anemia Some studies have shown that quality sleep contributes to the consolidation of a child's memory, learning ability, and creativity. This counseling was carried out at SD Negeri 200103 using lecture, observation, question and answer methods. The media used is in the form of posters and banners. The results of this counseling activity show that pupils of 200103 State Elementary School have understood the benefits of getting enough sleep for children. After this counseling is carried out, it is hoped that it can increase the knowledge of elementary school pupils about the importance of enough sleep for children in order to achive a properly and good sleep without obstacles by applying what has been conveyed during the counseling in daily life.